A "Religious Revolution" in Yehûd? : The Material Culture of the Persian Period as a Test Case - Frevel, Christian; Pyschny, Katharina; Cornelius, Izak (2014)
The present volume discusses the material culture of Persian Period Palestine/Israel against the background of Ephraim Stern’s hypothesis that Judah witnessed a “religious revolution“ during the transition between the (Neo)Babylonian and the Persian period, resulting in an imageless monotheism. The collection of essays originated in a workshop on “Jewish ‘Material’ Otherness? Ethnic, Religious and Cultural Boundaries in Late Persian and Early Hellenistic Times in the Southern Levant”, held at the Käte Hamburger KollegDynamics in the History of Religions between Asia and Europe (Ruhr-Universität Bochum) in 2010. Following an introductory overview on the material culture of the late Iron Age to the early Hellenistic period (Lester L. Grabbe), the most relevant object genres are reviewed in the light of new finds and current research: administrative stamp-seals (Oded Lipschits & David Vanderhooft), figurines (Izak Cornelius, Rüdiger Schmitt), incense burners (Christian Frevel & Katharina Pyschny), coins (Mary Joan Winn Leith, Patrick Wyssmann), seals and bullae (Silvia Schroer & Florian Lippke) and Greek pottery (Astrid Nunn). Special attention is devoted to regional developments in order to highlight commonalities and differences in the material culture between Yehûd and Samaria, and between Yehûd and the other neighbouring provinces. The volume demonstrates continuities and discontinuities in material culture, which mirror political, economic and historical developments. If the “religious revolution” thesis cannot be substantiated, the volume makes an important contribution to the history of religion of Persian Period Palestine/Israel with its nuanced discussion of Stern’s thesis and the new synopsis it offers of the material, and especially pictorial, culture of the period.